The effect of microemulsion method on the characteristics of Fe3O4/TiO2 material and its relationship with performance in methylene blue degradation: A Systematic Review - Fauziana Hidayat; Kormil Saputra; Dian Wijaya Kurniawidi (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2026)
TiO2-based photocatalysis offers a potential solution, but it has limitations, including high electron–hole recombination and difficulty in separating the catalyst after the reaction. The development of Fe3O4/TiO2 nanocomposites via the microemulsion method was conducted to enhance performance while facilitating catalyst separation. This study aims to examine the influence of the microemulsion method on material characteristics, characterization results, and their relationship to methylene blue degradation performance. The study was conducted using a systematic review with a PRISMA-compliant approach on literature from Scopus over the past 10 years. The selection process yielded five relevant articles. The microemulsion method was proven capable of producing nanoparticles (8–50 nm) with a homogeneous distribution and a mesoporous structure with a high surface area. XRD and SEM characterization results showed a dominance of the anatase phase or a mixture of anatase-rutile, which plays a role in enhancing charge separation. Photocatalytic performance showed a methylene blue degradation efficiency of up to approximately 90% within 60 minutes under sunlight. The improved performance was influenced by small particle size, high surface area, pore structure, and crystal phase composition. The addition of Fe3O4 has the potential to enhance electron transfer, suppress recombination, and facilitate catalyst separation through its magnetic properties. The microemulsion method plays a direct role in controlling the structure and characteristics of the material, which leads to improved photocatalytic performance of Fe3O4/TiO2 in the degradation of methylene blue.